Augmented Reality in the Industry: a Bibliometric Analysis - Pohlmann, Mayara Neves (2020)
This research aims to show a bibliometric analysis with the goal of presenting the studies about augmented reality in the industry. The current situation of the worldwide industry reflects an increasing search for new Technologies to assist in management of production following, therefore, the concept of continuous improvement presented by Lean Manufacturing. A large part of improvements implemented in processes is based on the pillars of industry 4.0. With the high competitiveness present in this situation, the implementation of augmented reality in different industrial segments has presented results that show that it provides important achievements in processes wich is a technique that solve problems of non-compliance and quality, train employees more effectively, assist in preventive maintence and even generates more safety. Therefore, based on the expansion of augmented reality in the industrial environment, the need to understand the main uses of this technology through a revision of scientific literature is justified. For the bibliometric analysis of this article, the chooses platform was Scopus and the chosen period was from 2015 to 2019. With this analysis, it was noted the diversity of augmented reality applications in different countries and industrial sectors.